The Chemresistive Properties of SiC Nanocrystalline Films with Different Conductivity Type: Experimental Results - A. V. Semenov; D. V. Lubov; A. A. Kozlovskyi (Innovations in Science and Technology Vol. 4, 2022)
We have demonstrated the ability of thin nanocrystalline SiC films with various types of conductivity to detect oxidative (O2), reducing gases (CO, CH4) with the maximum allowable concentrations for human safety. It was shown that n-nc-SiC films with electronic conductivity had a higher gas sensitivity Sn than p-nc-SiC films with hole conductivity sensivity Sp to the action of gases in a wide concentration range. So, for the maximum permissible concentrations of O2 (3%), CO (0.1%), CH4 (10%) the sensitivity ratio of the films Sn / Sp was 2.9; 4.8 and 10, respectively. For research, we used a simple resistor geometry optimizing which it is possible to significantly increase the sensitivity of films to gases in order to detect extremely low gas concentrations. Thus, based on nc-SiC films, it is possible to develop high-temperature gas sensors to detect reactive gases in a wide range of concentrations, including threshold allowable values.